FRP-brick masonry bond degradation under hygrothermal conditions - Maljaee, Hamid (2016)
Externally bonded reinforcement (EBR) of masonry structures with Fiber Reinforced Polymers (FRPs) has received extensive attention during the last years. Despite the vast literature on mechanics and short-term performance, the durability and long-term performance of these systems still remain insufficiently studied. Structures are subjected to harsh environments such as coupled temperature and moisture variations (hygrothermal conditions) during their service life. A clear understanding on the performance of the strengthening system under these conditions is critical at the design stage.This paper presents an experimental investigation on the effect of long-term hygrothermal conditions on FRP-strengthened masonry components. The focus is on the interfacial bond behavior and materials mechanical properties. The effect of mechanical surface treatment on the bond durability is also investigated.